2020
DOI: 10.11646/zootaxa.4851.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Tardigrades of Finland: new records and an annotated checklist

Abstract: Species checklists are powerful and important tools of communication between taxonomists and applied environmental biologists, which in turn lead to well-planned and successful conservation strategies and ecological studies. Despite this, only recently the interest on compiling systematic checklists is growing among taxonomists who study tardigrades—micrometazoans that inhabit almost every habitat worldwide. As the Finnish records of tardigrades (a.k.a. water bears) species are incomplete, outdated and no chec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Specifically, biodiversity studies and taxonomic checklists need precise taxonomic identifications to be comparable across different geographical areas. However, as noted, e.g., by [ 82 ], numerous identifications cannot be confirmed due to the presence of (pseudo) cryptic species complexes. Furthermore, biogeographical studies supported by molecular data on tardigrades are still scarce.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, biodiversity studies and taxonomic checklists need precise taxonomic identifications to be comparable across different geographical areas. However, as noted, e.g., by [ 82 ], numerous identifications cannot be confirmed due to the presence of (pseudo) cryptic species complexes. Furthermore, biogeographical studies supported by molecular data on tardigrades are still scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Species of the Macrobiotus pallarii complex are not commonly found, but the complex has a wide, possibly global distribution. Although the majority of records are concentrated in Europe (Finland, Greece, Hungary, Italy, Montenegro, Norway, Poland, Republic of Bulgaria, Russian Federation, Turkey, Yugoslavia [ 25 , 82 , 96 – 98 ]), there are also reports from Asia (North Korea, Russian Federation [ 25 ]), North America (United States, Cayman Islands [ 28 , 86 88 ]), and Africa (Democratic Republic of the Congo, Swaziland [ 27 , 92 ]). In light of our findings, all these records except the type localities should be considered dubious and be designated as species of the Macrobiotus pallarii complex, i.e., as Macrobiotus aff.…”
Section: Discussionmentioning
confidence: 99%
“…Other faunistic studies, comparable in sampling effort and substrate diversity, found lower diversity, e.g. 26 species in 32 samples, ratio 0.81 (Marche-Umbria, Italy) 61 , 23 species in 48 samples, ratio 0.47 (Sardinia, Italy) 62 , 41 species in 60 samples, ratio 0.68 (Great Smoky Mountains National Park, TN-NC, USA) 60 , 10 species in 13 samples, ratio 0.76 (Jyväskylä, Finland) 58 . Therefore, this study indicates a high biodiversity of tardigrades in the KVBR, as suggested by the presence of many genera, species, and new taxa from different environments and habitats (i.e.…”
Section: Discussionmentioning
confidence: 96%
“…The species abundance of tardigrades has been shown to be mostly related to the sampling effort, rather than to the surface of the sampling area 58 . The limited number of visited sites and limited sampling effort (34 samples collected in five sites of a 1050 km 2 area) of our study suggest that the true tardigrade biodiversity of KVRB is much higher than recorded, and that there are considerably more tardigrade species to be found in this area.…”
Section: Discussionmentioning
confidence: 99%
“…On the island of Crete, 28 species (from more than 150 samples) have been listed based on two sampling campaigns alone (Maucci and Durante Pasa 1982). Taking into consideration recent progress in tardigrade taxonomy and faunistic studies brought about by the integrative approach, it is more than likely that the region exhibits higher species diversity and additional sampling effort may reveal more species (Vuori et al 2020).…”
Section: Introductionmentioning
confidence: 99%